Revisiting the MotionWatch8©: Calibrating Cut-Points for Measuring Physical Activity and Sedentary Behavior Among Adults With Stroke - Falck, Ryan S.; Best, John R.; Li, Michael C. R.; Eng, Janice J.; Liu-Ambrose, Teresa (Frontiers in Aging Neuroscience, 2019)
Poor sleep quality, low physical activity (PA), and high sedentary behaviour (SB) are common following stroke, which can limit stroke recovery and contribute to greater cognitive decline post-stroke. There is also increasing evidence that sleep quality, PA, and SB are dynamically related to each other and to cognitive health. Hence, the sleep quality, PA, and SB of adults with stroke should be measured concurrently using objective methods. One currently available method for objectively measuring PA, SB, and sleep is the MotionWatch8© (MW8), a wrist-worn accelerometer we have previously shown has evidence of validity and reliability for healthy older adults. However, adults with stroke can have significant mobility restrictions (depending on stroke severity) and thus it is important to determine separate PA and SB cut-points for adults with stroke, as well as validate separate cut-points 1) when the MW8 is worn on the stroke affected side compared to the non-affected side; and 2) for adults with mild stroke versus adults with moderate-to-severe stroke. In the current study, we concurrently measured MW8 actigraphy (worn on both the stroke affected side and the non-affected side) and indirect calorimetry during 10 different activities of daily living for 43 adults with stroke (aged 55-87 years). Using intra-class correlations, we first investigated the reliability and consistency of the MW8 when placed on the stroke affected side as compared to the non-affected side for 1) all participants irrespective of stroke severity; 2) participants with mild stroke, classified as a Fugl Meyer motor score of ≥ 79/100; and 3) participants with moderate-to-severe stroke (i.e., Fugl Meter < 79/100). We then determined cut-points for all participants—as well as separate cut-points based on stroke severity—on both the stroke affected side and non-affected side for SB, light PA, and moderate-to-vigorous PA using receiver operating characteristic curves. Our results support using different cut-points for the stroke affected side vs. non-affected side, and for different levels of stroke severity. Hence, these data provide a new measure for concurrently examining the dynamic relationships between PA, SB, and sleep quality among adults with stroke.